Foreign Direct Investment di 3 Negara Asia Tenggara Periode 2005 – 2020 - Maryam Rifa Azzahra (WIDA Publishing, 2022)
Investment is one of the most important indicators of a country's development because investment can increase cash flow, and stabilize the economy, especially in developing countries such as Indonesia, Malaysia, and Thailand. This study aims to analyze the effect of inflation and exchange rates on Foreign Direct Investment (FDI) in 3 Southeast Asian countries, namely Indonesia, Malaysia, and Thailand, during 2005 - 2020. The data used is secondary data obtained from the World Bank website. Data were analyzed using a panel data regression model. The study found that inflation had a positive and significant effect on foreign direct investment, while the exchange rate had no significant impact.